Development of SNP markers for grain yield screening of Brazilian rice cultivars - Pantalião, Gabriel Feresin; Vianello, Rosana Pereira; Bueno, Luíce Gomes; Mendonça, João Antônio; Coelho, Alexandre Siqueira Guedes; Cordeiro, Antônio Carlos Centeno; Valdisser, Paula Arielle; Vieira, Ariadna Faria; Brondani, Claudio (Pesquisa Agropecuaria Brasileira, 2020)
The objective of this work was to identify and validate single-nucleotide polymorphism (SNP) markers related to grain yield in rice (Oryza sativa) core collection. The genome-wide association studies (GWAS) methodology was applied for genotyping of 541 rice accessions by 167,470 SNPs. The grain yield of these accessions was estimated through the joint analysis of nine field experiments carried out in six Brazilian states. Fifteen SNPs were significantly associated with grain yield, and out of the ten SNPs converted to TaqMan assays, four discriminated the most productive accessions. These markers were used for the screening of rice accessions with favorable alleles. The selected accessions were, then, evaluated in field experiments in target environments, in order to select the most productive ones. This screening reduces the number of accessions evaluated experimentally, making it possible to prioritize those with higher productive potential, which allows of the increase of the number of replicates and, consequently, of the experimental accuracy.